Changes to reproductive endocrinology and infertility practice, research, and training as investor mergers increase - Farrah L. Saleh, M.D.; Eli Y. Adashi, M.D., M.S.; David B. Sable, M.D.; Vitaly A. Kushnir, M.D.; Hugh S. Taylor, M.D. (F&S Reports, 2023)
Private equity investment in fertility clinics has rapidly increased and is leading to unprecedented changes in the field of reproductive endocrinology and infertility (REI). The goal of this paper was to review private equity’s current integration in REI and discuss both benefits and challenges of investor involvement. We found that at least 25% of fellowship programs and medical schools were affiliated with private practice fertility clinics, not free-standing academic clinics. Approximately half of medical schools and nearly all REI fellowship programs that were affiliated with private practices were also backed by private investors. Research participation remains robust in private equity-affiliated REI clinics. With the changing infrastructure, we discuss the potential influence on trainee experience and research while also acknowledging the unique advantages that investor involvement may offer.